Alat Ukur Power Menendang Futsal Berbasis Mikrokontroler - Saputra, Ahmad Fauzi; Fitranto, Nur; Wardoyo, Hendro (Jurnal Kepelatihan Olahraga, 2024)
The development of a kicking power measurement tool in futsal is crucial, considering the effectiveness of measurements in sports plays a significant role in achieving peak performance. This research aims to develop a futsal kicking power measurement tool based on microcontroller technology. The research method used is Research and Development with the ADDIE model. The five steps involved in developing this model include analysis, design, development, implementation, and evaluation. The research sample consisted of 15 U-15 futsal athletes from Rusun Rawa Bebek. The research findings show that the athletes' perception of the developed tool indicates that this kicking power measurement tool is "Very good." Based on this research, it can be concluded that the development of this kicking power measurement tool is an effective tool for Indonesian coaches to measure the accuracy of kicking power and passing strength in futsal, thus making it highly suitable for widespread use.